2020
DOI: 10.3390/ijms21051794
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mono-n-Butyl Phthalate in Women with Endometriosis and Its Association with the Biological Effects on Human Granulosa Cells

Abstract: To study the association between urinary phthalate metabolite levels, endometriosis, and their effects on human granulosa cells, we recruited patients who underwent laparoscopy to confirm endometriosis (n = 123) and control patients (n = 78). Liquid chromatography–tandem mass spectrometry was used to measure the following five urinary phthalate metabolites: mono-n-butyl phthalate (MnBP), mono(2-ethylhexyl) phthalate, monobenzyl phthalate, mono(2-ethyl-5-oxo-hexyl) phthalate, and mono(2-ethyl-5-hydroxyhexyl) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 74 publications
0
20
0
2
Order By: Relevance
“…In our study, the eQTL was performed on the total of 78 tissue samples for endometriosis patients with recorded SNP genotypes. The expression of inturned planar cell polarity protein ( INTU ) was detected by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and been described in detail elsewhere 31 . Glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) mRNA was amplified using q-PCR with the forward primer 5′-gagtccactggcgtcttcac-3′ and reverse primer 5′-gttcacacccatgacgaaca-3′.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the eQTL was performed on the total of 78 tissue samples for endometriosis patients with recorded SNP genotypes. The expression of inturned planar cell polarity protein ( INTU ) was detected by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and been described in detail elsewhere 31 . Glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) mRNA was amplified using q-PCR with the forward primer 5′-gagtccactggcgtcttcac-3′ and reverse primer 5′-gttcacacccatgacgaaca-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Some other epidemiologic studies have focused on the higher BPA level in women with polycystic ovarian syndrome (PCOS) [ 24 , 25 ] and the consistent conclusion can be also found in adolescents [ 26 ]. In addition, various cell cultures [ 27 ], animal models [ 28 ], and human epidemiologic data have supplied evidences that phthalates may change the endometrial environment or are possibly associated with endometriosis [ 29 ]. One recent study has described that BPA exposure may affect the expression of key severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection mediators such as angiotensin-converting enzyme 2 (ACE2), transmembrane serine protease 2 (TMPRSS2), and furin in human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have shown that phthalates, after entering the body, cause disorders of the endocrine system. They can also contribute to the development of allergies, asthma, obesity, metabolic syndrome, type 2 diabetes, cardiovascular diseases, and malignant neoplasms, and all these disorders are associated with oxidative stress induction [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%